Institute of Book Industry - Thompson, Charles Odotei (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of Postgraduate Diploma in Architecture.